242 Transdermal flunixin meglumine minimally alters neutrophil functionality in beef heifers administered a respiratory disease challenge. (7th December 2018) - Word, A; Broadway, P; Liang, Y; Newcomb, H; Burdick Sanchez, N; Capik, S; Littlejohn, B; Holland, B; Ellis, G; Fuselier, J; Hutcheson, J; Ballou, M; et al.
Abstract: The objectives were to determine the effects of altering time of transdermal flunixin meglumine (BTD; Banamine Transdermal, Merck Animal Health) administration relative to a viral-bacterial challenge in beef heifers. Thirty-two heifers (170 ± 21.1 kg BW) were assigned to one of four treatments: 1) Control (CON), receiving no BTD, 2) Arrival (ARR), receiving BTD the day after arrival (-144h; 3.33 mg/kg BW), 3) Viral (VIR), receiving BTD at viral challenge (-72h), or 4) Bacterial (BAC), receiving BTD at bacterial challenge (0h). At -72h, all cattle received 1x108 PFU bovine herpesvirus-1 (BHV-1) intra-nasally and returned to outdoor group-pens. At 0h, all cattle were challenged intra-tracheally with 1.18x106 CFU average dose of Mannheimia haemolytica, fitted with an indwelling jugular catheter, and moved to individual stanchions. Whole blood was collected at -144, -72, 0, and 72h relative to M. haemolytica challenge. Data were analyzed using the Mixed procedure of SAS specific for repeated measures with fixed effects of treatment, time, and their interaction. A treatment×time interaction tended (P = 0.07) to occur for neutrophil oxidative burst capacity (OB). Non-orthogonal contrasts revealed that OB decreased (P ≤ 0.005) in ARR and VIR at 0h compared to (BAC + CON)/2. A treatment×time interaction also tended to occur (P = 0.09) for phagocytic activity, and ARR tended (P = 0.07) to be decreased at 0h when compared to (BAC + CON)/2. Finally, a treatment×time interaction (P = 0.004) occurred for change in neutrophil L-selectin expression, whereas expression was decreased among VIR at 0h (P = 0.001) and BAC at 72h (P = 0.09) when compared to all other treatments at those sample times. These data indicate that BTD applied before or during a respiratory disease challenge may reduce neutrophil function, which provides evidence that flunixin meglumine may reduce neutrophil-associated inflammation.